PENGARUH TINGKAT PENDAPATAN, PENDIDIKAN DAN TANGGUNGAN KELUARGA TERHADAP KEPATUHAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN PERKOTAAN DI KECAMATAN ILIR TIMUR II PALEMBANG - Meti Zuliyana (JURNAL KOMPETITIF, 2012)
This study essentially discusses the influence of income level, education, and dependent families against society of compliance in paying taxon land and buildings in the district II East Ilir Palembang. In order to produce realiable information to assist the tax office, tax collector officials and other relevant parties, the object of this study is the taxpayer in the district II East Ilir Palembang. Systematic and accurate picture is obtained by collecting by collecting, classifying, assessing, analyzing, and make a confirmation of the hypotheses or draw conclusions objectively some of the problems examined. The method used random sample ( random ). In analyzing the data used multiple regresion analysis, then by looking at the effect of simultaneously (F) or partial ( t ) of the object under study. After the analysis process by using the above method can be concluded there is influence of income level, education, and Dependent Families Against Society of Compliance In Paying Tax on Land and Buildings in the District II East Ilir Palembang.Key words: Rate Income, Education, and Dependent Families In Society of Compliance Againts Paying The United Nations.